(untitled) (Swiss Medical Weekly, 2025)
Glucagon-like peptide-1 receptor agonists are increasingly used in the management of obesity and diabetes. Their potential risks, however, particularly regarding pancreatitis and pancreatic cancer, remain contentious. Despite numerous studies and meta-analyses indicating no significant correlation between GLP-1 RA therapy and the incidence of acute pancreatitis or pancreatic cancer, gaps in the literature persist regarding their effects in patients with frequent pancreatic conditions, such as intraductal papillary mucinous neoplasms, a disease with potential for malignant transformation. Further rigorous clinical studies addressing the safety of GLP-1 receptor agonists in patients with intraductal papillary mucinous neoplasms should be conducted to understand the potential risks and benefits, establish clear guidelines for clinical practice and ultimately ensure the safety of these medications in this potentially vulnerable patient population.